Premanisme Lahan Parkir Pasar Wameo: Analisis Penegakan Hukum Menurut Lawrence M. Friedman - Yusri; Asrianto Zainal; Aris Darmawan Al Habib (Institut Agama Islam (IAIN) Kendari, 2025)
Gangsterism is still rampant against several people who work as illegal parking attendants at Wameo Market. In fact, the special parking area at Wameo Market is a parking lot managed by the government. This study aims to determine the Baubau Police's policy regarding gangsterism in parking lots and to determine law enforcement against gangsterism in parking lots at Wameo Market from the perspective of Lawrence M. Friedman. This study is an empirical research using a legal approach and case study methodology. Data collection techniques include observation, interviews, and documentation. The results of this study indicate that the Baubau Police Department's policy in addressing parking lot thuggery at Wameo Market involves public awareness campaigns, forming a task force to combat thuggery, and enforcement operations. Law enforcement against parking lot thuggery at Wameo Market, based on Lawrence M. Friedman's theoretical perspective, is divided into three categories: First, the legal substance used to address parking lot thuggery at Wameo Market is adequate and comprehensive. Second, the legal structure in this case, namely the actions taken by the Wolio Police Station and the Transportation Department, is sufficiently good. The Wolio Police Station implements preemptive, preventive, and repressive measures, including public awareness campaigns, patrols, and raids. Meanwhile, the Transportation Department is undertaking efforts to organize and supervise parking lots, set parking fees and levies, and legalize illegal parking attendants. Third, the legal culture of the community at Wameo Market is still relatively weak due to the low level of legal knowledge and understanding among the community, which has led to the prevalence of parking lot thuggery that frequently occurs. Keywords: Law Enforcement; Thuggery; Parking Lots